PHONOCARDIOGRAM MONITOR VIA BLUETOOTH WIRELESS NETWORK - มาตรมูล ไกรลาส; คล้ายใจตรง อภิญญา; พันไพศาล วสุ (PSRU Journal of Science and Technology, 2018)
This research designs and constructs phonocardiogrammetric device with bluetooth connectivity. A modified stethoscopes with miniaturized condenser microphone is used as a tool for retrieving cardio phonogram data. The analog sound is then amplified with non-inverting amplifier with the gain of 47:1 and low-pass filter with 1 kHz cut-off frequency. An analog cardiophonogram data is then converted to digital by arduino nano reduce instruction set computing. Finally, the bluetooth module HC-05 is used to transfer digital cardiophonogram to an application installed on the target mobile device. A cardiophonogrammetric display application uses Basic4Android as a tool to achieve graphical plot of digital data transferred from HC-05 module. It was found that the digital data transferred from phonocardiogrammetric device to the mobile phone is wireless, clear and correct.